No Impact of Omega-3 Fatty Acid Supplementation on Symptoms or Hostility Among Patients With Schizophrenia - Qiao, Yi; Liu, Cai Ping; Han, Hui Qin; Liu, Feng Ju; Shao, Yang; Xie, Bin (Frontiers in Psychiatry, 2020)
Objective: This study was aimed to explore the impact of fish oil on hostility and psychopathology among acute violent patients with schizophrenia. Method: 67 acute hospital patients demonstrating violent behavior in the context of schizophrenia illness, treated with antipsychotics, were randomly assigned to supplement with either Omega-3 fatty acids (N=32) or placebo (N=35) in a double-blind, placebo-controlled trial. Assessments were conducted at baseline, week 4 and week 8. Results: The symptoms and hostility decreased after treatment for 4 weeks and 8 weeks in both groups, but there were no group differences. Conclusions: current study didn’t find the extra benefits on symptoms and hostility from Omega-3 fatty acid supplementation in patients with schizophrenia. It implied that Omega-3 fatty acids might not be necessary for reducing psychopathology and hostility in the acute patients with schizophrenia.